Language policy and governance: the Pontius Pilate example (2017)
Pontius Pilate's trilingual inscription on the cross of Jesus Christ has received considerable scholarly attention from different perspectives. However, none of such studies has taken a sociolinguistic perspective in the analysis of the inscription. Adopting the Socio-linguistic theory of language planning as theoretical framework, this study employed the tools of linguistic criticism to analyse Pilate's inscription, “Jesus of Nazareth, the King of the Jews”, in order to examine the probable reasons behind Pilate's use of three languages to write the inscription and the implication of the title 'King' within the socio- cultural setting and antecedent linguistic history of the Jews at that time. Primary data were drawn from the King James Version of the Bible; the text of the New Testament in Modem Hebrew, the New Testament in the original Greek, Byzantine Text Form, and the Latin Vulgate. Hebrew was the religious language of Judaism; Greek was the lingua franca and Latin was the language of Roman imperialism, especially in governance and jurisdiction at that time. The title 'King' was associated with the Jewish hope of a messianic conquering king. The Romans held the title in contempt since their last king before the Republic was deposed. The use of Hebrew, Greek and Latin by Pilate has sociolinguistic implications reflecting the status of the three languages. The study recommends that contemporary political leaders should promote Nigeria's indigenous languages in addition to the English language for effective communication in governance